Novel SrTi1-xFexO3 nanocubes synthesized by microwave-assisted hydrothermal method - da Silva, Luis F.; Avansi, Waldir [UNESP]; Moreira, Mario L. [UNESP]; Andres, Juan; Longo, Elson [UNESP]; Mastelaro, Valmor R. (Royal Soc Chemistry, 2012)
We report herein for the first time a facile synthesis method to obtain SrTi1-xFexO3 nanocubes by means by a microwave-assisted hydrothermal (MAH) method at 140 degrees C. The effect of iron addition on the structural and morphological properties of SrTiO3 was investigated. X-ray diffraction measurements show that all STFO samples present a cubic perovskite structure. X-ray absorption spectroscopy at Fe absorption K-edge measurements revealed that iron ions are in a mixed Fe2+/Fe3+ oxidation state and preferentially occupy the Ti4+-site. UV-visible spectra reveal a reduction in the optical gap (E-gap) of STFO samples as the amount of iron is increased. An analysis of the data obtained by field emission scanning electron microscopy points out that the nanoparticles present a cubic morphology independently of iron content. According to high-resolution transmission electron microscopy results, these nanocubes are formed by a self-assembly process of small primary nanocrystals.